Influence of feet position and execution velocity on muscle activation and kinematic parameters during the inclined leg press exercise - Martín-Fuentes, I.; Oliva-Lozano, J. M.; Muyor, J. M. (Sports Health: A Multidisciplinary Approach, 2021)
Background: The leg press is one of the most typical exercises for strengthening the lower limbs. The objectives of this study were to compare 5 inclined leg press exercise conditions, varying the feet width stance (100% or 150% hip width), the feet rotation (0° or 45° external rotation) on the footplate and using 2 different movement velocities (MVs; maximum intended, and 2:2 seconds steady-paced velocities) to determine their effect on muscle activation as well as on the kinematic parameters between trained men and trained women.